LEGALITY OF LEGAL ENTITIES OF VILLAGE OWNED ENTERPRISES (BUMDES) POST LAW NUMBER 11 OF 2020 CONCERNING JOB COPYRIGHT - Dewi, Feni Nur Fitria; Nurhayati, Nunik; Enggarani, Nuria Siswi; Muttaqin, Labib (Khairun Law Journal, 2023)
This research aims to discuss the background to the policy on the obligation to change Village-Owned Enterprises (BUMDes) from business entities to legal entities and the development of BUMDes legal entity status in Banyudono District, Boyolali Regency. Law Number 11 of 2020 concerning Job Creation in Article 117 amends Article 1 (6) of Law Number 6 of 2014 concerning Villages. Before the changes to the Village Law, BUMDes were described as business entities, whereas in the Job Creation Law BUMDes were described as legal entities. The research method used is empirical juridical, located in Banyudono District, Boyolali Regency, Central Java. The results of the discussion showed that 1) The aim of the promulgation of Article 117 of the Job Creation Law is to be able to absorb the widest possible Indonesian workforce amidst increasingly competitive competition and the demands of economic globalization, including at the village level by optimizing BUMDes. 2) In Banyudono District, Boyolali Regency, there are 15 (fifteen) villages and only 5 (five) BUMDes, but there are 2 (two) BUMDes that have not yet been incorporated, namely BUMDes Banyudono and BUMDes Hamlet.